FORMATION OF ELECTRICAL ENGINEERING AS A SCIENCE AND ACADEMIC DISCIPLINE - Pazilova , Shokhida Abdulbasitovna (Educational Research in Universal Sciences, 2023)
This article discusses the development and formation of electrical engineering as a science and academic discipline. It also tells about how extremely important electrical installations have become in the life of modern society, in which electrical and magnetic phenomena are used to implement a variety of technological processes.